Rancang bangun sistem penunjang keputusan nilai tambah rantai pasok agroindustri bunga matahari - Nunung Nurhasanah; Isna Ibnah Mudrikah; Ginang Natilla Adlina; Ahmad Chirzun; Iphov Kumala Sriwana (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Sunflowers are commodities with the potential to be developed into derivative products such as cooking oil, herbal oil, animal feed, and even biodiesel. However, stakeholders in the sunflower agro-industry, from farmers to producers of derivative products, still face several challenges in creating the best practices for sunflower agro-industry. These challenges include the underutilization of technology and the application of supply chain management. Therefore, this research focuses on designing a prototype decision support system for value added products in the sunflower agro-industry supply chain network. The purpose of this research is to support stakeholders in making informed decisions regarding the production of sunflower derivative products, including cooking oil, herbal oil, and animal feed. The development of this decision support system design utilizes the system development life cycle (SDLC) method with a waterfall model. The prototype design results employ the Just in Mind application for creating a graphical user interface and will be implemented on smartphones using the Android system. This research is limited to supporting decision-making in the value-added model of the sunflower agro-industry supply chain. The implementation of the system is considered a subsequent stage in future research. Additionally, the addition of other models is expected to be developed in future studies.